Sistem Informasi Destinasi Wisata Bulukumba Explore Berbasis Website - Amran, Nur Fadillah; Barda, Nur Isnaniya; Arafah, Luthfiyah Ramadhani K.; Syukur, Pramudya Asoka (PT. Lontara Digitech Indonesia, 2024)
The lack of available information regarding tourist destinations in Bulukumba Regency causes difficulties for tourists in exploring the area optimally. This study aims to develop a web-based tourism information system that can facilitate users in accessing and exploring tourist destinations in Bulukumba Regency. This research employs a qualitative method with a descriptive-analytical approach to design and develop this system. The development results indicate that this information system can effectively provide features such as destination profiles, locations, ratings, and tourist reviews. Functional and non-functional testing shows that the system operates according to user expectations, although some technical issues need to be addressed in the future. With this information system, it is expected to enhance tourism promotion and local revenue through increased economic activity in the tourism sector.